Diary of a wimpy kid : old school - Kinney, Jeff (New York : Amulet Books, 2015)
Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive?
Keywords: Electronics -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction; Electronics -- Fiction; Families -- Fiction; Diaries -- Fiction; Humorous stories